2003
DOI: 10.1161/01.hyp.0000079309.68998.65
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Vascular Structural Changes During and After Short-Term Antihypertensive Treatment

Abstract: Abstract-The present study characterized the persistent changes (ie, off-treatment) resulting from short-term antihypertensive treatments on mean arterial pressure (MAP) and structurally based vascular resistance. Rats were treated for 14 days with enalapril (30 mg · kg Ϫ1 · d Ϫ1 ) with regular (ENAL, 0.4%) or low salt (ELS, 0.04%) diets, or a triple therapy (Triple: hydralazine 45 mg · kg Ϫ1 · d Ϫ1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 47 publications
2
32
0
2
Order By: Relevance
“…Concentrations were determined based on average body weight and water consumption per cage, and adjusted every 5-6 days to account for changes in body weight and daily water consumption, as previously described. 9,10 Rats had ad libitum access to food and water throughout the treatment period. The dose and duration of enalapril treatment was based on previous studies where we demonstrated persistent reductions in blood pressure and LV mass following cessation of treatment 9 and apoptosis-mediated reduction of cardiac fibrobasts in the LV.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations were determined based on average body weight and water consumption per cage, and adjusted every 5-6 days to account for changes in body weight and daily water consumption, as previously described. 9,10 Rats had ad libitum access to food and water throughout the treatment period. The dose and duration of enalapril treatment was based on previous studies where we demonstrated persistent reductions in blood pressure and LV mass following cessation of treatment 9 and apoptosis-mediated reduction of cardiac fibrobasts in the LV.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…9,10 Rats had ad libitum access to food and water throughout the treatment period. The dose and duration of enalapril treatment was based on previous studies where we demonstrated persistent reductions in blood pressure and LV mass following cessation of treatment 9 and apoptosis-mediated reduction of cardiac fibrobasts in the LV. 5 A 14-day washout period following enalapril treatment based on previous assessments demonstrating that blood pressure stabilizes at a new baseline B7-10 days following cessation of treatment.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the duration of the cardiovascular effects after treatment withdrawal. Various long-term and also some short-term antihypertensive treatments have been shown to induce persistent changes in blood pressure and cardiovascular structure weeks after treatment removal (38). Therefore, an important question that needs to be addressed is whether the withdrawal of LGF treatment would or not maintain the reduction of blood pressure and the regenerative cardiovascular actions.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The concept that long-term antihypertensive therapy with angiotensin-converting enzyme (ACE) inhibitors has been proven to induce both a regression of vascular structure and a reduction in mean arterial pressure, has been recently questioned. 8 Further, the vascular changes that persist off-treatment have been proposed to result from extended inhibition of the trophic actions of angiotensin II, prolonged reduction in mean arterial pressure or from combined effects. Recent evidences suggest that aggressive short-term antihypertensive as well as lipid-lowering therapy with 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) may induce structural remodeling of the penile vasculature.…”
Section: Introductionmentioning
confidence: 99%